(untitled) (Al-Academy, 2024)
The study tagged ( the intellectual implications of the realistic Fine works of art) is a scientific effort to detect modest intellectual and artistic dimensions of the artwork realistic plastic , through some selected artistic productions of the painted work of art of the Iranian artist Ayman al - Maliki , with the result that the researcher collects materials to serve the scientific research topic which comes in three chapters.First chapter included the general framework of the research (the promise of the research problem and its significance, objectives and limits and some of the terms contained therein). Second chapter of this research was specified to the theoretical framework which included some of the topics that are directly related to the subject of the search, Has dealt a researcher at the first axis thereof subject (content in the artwork) as a component intellectually and psychologically important is established from which the general meaning of the product of technical plastic, Second axis has included the subject (reference the intellectual work of art), in terms of the mental images printed our the advantage of being able to be reflected on each other to ride new and different ideas through the process of thinking, including the operations are of intellectual perception within the human imagination, on the grounds that the imagination is expressed passes through it who wants to explain the creative process, through the third axis the researcher explained the concept of realism in art , which constitutes the basic building block for the main title search , with all the intake of the concepts and uses realistic because from the very beginning was the driving force in the evolution of art, through the fourth axis researcher (stylistic Artist Ayman al-Maliki ) with a brief autobiography .Chapter three contained the research procedures, including the contents of the (community of search and selection of samples and search tool, tool building and sincerity, and then analyze the samples). Finally, specifically in the (fourth quarter) of this research has been reached to search results through the analysis of the samples and in the light of what has been determined goals. The most important of which was: - Were not in the use of classical realism in fine art paintings aesthetic purposes, but there are ideological purposes (graphical) were sentimental or self- belonging to the terms of reference of the artist himself.- The realistic approach in the implementation of works of art is the closest (Aware) for the recipient because it contributes effectively to build bridges of communication between him and the intellectual artist.- it is often realized aesthetic goals of the work of art through the ease of understanding of intellectual contents receiver expressive away from the complexities of the amounts by some modern and contemporary artists.- If the use of artistic touches technically to Fine art painting (realism) Added aesthetic values that will elevate it to the level of creativity.- The method of photography in painting (realistic) is a concept that addresses optical image to molecules provided by the expressive value of art and aesthetic. Which is not quoting a reproduction of an abstract image for mere beauty, but beauty is meaningless.